Impact of treatment and clinical characteristics on the survival of children with medulloblastoma in Mexico - Salceda-Rivera, Violeta; Tejocote-Romero, Isidoro; Osorio, Diana S.; Bellido-Magaña, Rosalba; López-Facundo, Araceli; Anaya-Aguirre, Susana E.; Ortiz-Morales, Daniel; Rivera-Luna, Roberto; Reyes-Gutiérrez, Evelyne; Rivera-Gómez, Rebeca; Velasco-Hidalgo, Liliana; Cortés-Alva, Deyanira; et al. (Frontiers in Oncology, 2024)
Introduction: Data on medulloblastoma outcomes and experiences in low-and middle-income countries, especially in Latin America, is limited. This study examines challenges in Mexico's healthcare system, focusing on assessing outcomes for children with medulloblastoma in a tertiary care setting. Methods: A retrospective analysis was conducted, involving 284 patients treated at 21 pediatric oncology centers in Mexico. Results: High-risk patients exhibited markedly lower event-free survival than standard-risk patients (43.5% vs. 78.3%, p<0.001). Influential factors on survival included anaplastic subtype (HR 2.4, p=0.003), metastatic disease (HR 1.9, p=0.001); residual tumor >1.5cm², and lower radiotherapy doses significantly impacted event-free survival (EFS) and overall survival (OS). Platinum-based chemotherapy showed better results compared to the ICE protocol in terms of OS and EFS, which was associated with higher toxicity. Patients under 3 years old displayed notably lower OS and EFS compared to older children (36.1% vs. 55.9%, p=0.01).